A panel of cancer-testis genes exhibiting broad-spectrum expression in haematological malignancies - Liggins, A; Lim, S; Soilleux, E; Pulford, K; Banham, A (2010)
Cancer-testis (CT) antigens/genes show restricted expression in normal tissues but widespread expression in many tumour types. This, coupled with their ability to induce cytotoxic T-lymphocyte responses, makes them attractive vaccine candidates. Following our identification of PASD1, we have used RT-PCR to analyse the mRNA expression profile of a large panel of CT genes in cell lines derived from haematological malignancies, and have studied Sp17 protein expression in the same cell lines and diffuse large B-cell lymphoma (DLBCL) biopsies. Our extensive analysis revealed multiple CT transcripts exhibiting widespread expression across cell lines derived from 21 B- and 4 T-cell malignancies. The broadest mRNA expression profiles were observed for the following eight CT genes: Sp17 (25/25), PRAME (25/25), CSAGE (24/25), PASD1 (22/25), CAGE/DDX53 (19/25), CTAGE1 (19/25), HAGE/DDX43 (16/25) and PLU-1/JARID1B (15/25). Cell lines derived from more aggressive lymphoma subtypes generally expressed CT transcripts at higher frequency. Sp17 protein was detected in a number of cell lines and in six of eleven (54.5%) DLBCL biopsies. Analysis of Sp17 protein expression, by immunohistochemistry and Western blotting, broadens the scope of this CT antigen as a potentially relevant clinical target in haematological malignancies. Further studies of protein expression are now needed to validate these antigens as vaccine candidates. © 2010 by Alison H. Banham.